Assessment of the application of oxygen enrichment in the hydrogen-fueled Wankel rotary engine. (1st June 2023) - Meng, Hao; Ji, Changwei; Yang, Jinxin; Wang, Shuofeng; Gao, Chunlei; Shen, Xuesong; Xin, Gu; Hong, Chen
Highlights: The application of O2 enrichment in a hydrogen Wankel rotary engine is assessed. O2 enrichment can improve power output with penalties in efficiency and emission. O2 -enriched level can effectively accelerate the heat release process. O2 enrichment will lead to knock, backfire and pre-ignition. Low O2 -enriched levels has higher application value than high O2 -enriched levels. Abstract: Hydrogen-fueled Wankel rotary engines (WREs) with excellent dynamic and emission characteristics have the potential to become a substitute for current fossil-fueled reciprocating piston engines. Oxygen enrichment can be employed to solve the lower power of hydrogen-fueled internal combustion engines, however, it has not been applied in hydrogen-fueled WRE at present. Hence, the goal of this work is to experimentally assess the application of oxygen enrichment in the hydrogen-fueled WRE. This work is conducted at 1500 r/min, wide-open throttle and 2.0 excess air ratio. The work found that within the test range, oxygen enrichment can effectively improve the brake torque of hydrogen-fueled WRE, however, penalize the brake thermal efficiency and NO emission. When the oxygen fraction in air increases from 21% to 29.1%, the brake torque is increased by about 45% while the brake thermal efficiency is lowered by about 8.5% and NO emission deteriorates by three orders of magnitude. Oxygen enrichment can accelerate flame development and propagation process. Besides, as the oxygen-enriched level is increased, abnormal combustion, including knock, backfire and pre-ignition, began to occur and affected the normal operation of hydrogen-fueled WRE. In general, compared with the high oxygen-enriched level, which has severe penalties on performance except for power output, low oxygen-enriched level has higher application potential.